Pleiotropic Effects of Tetracyclines in the Management of COVID-19: Emerging Perspectives - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Alqarni, Mohammed; Cruz-Martins, Natália; El-Saber Batiha, Gaber (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (Covid-19) is a global infectious disease caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). Approximately, 15% of severe cases require an intensive care unit (ICU) admission and mechanical ventilation due to development of acute respiratory distress syndrome (ARDS). Tetracyclines (TCs) are group of bacteriostatic antibiotics, like tetracycline, minocycline, and doxycycline, effective against aerobic and anaerobic bacteria as well as Gram-positive and Gram-negative bacteria. Based on available evidences, TCs may be effective against coronaviruses, and thus useful to treat COVID-19. Thus, this review aims to provide a brief overview on the uses of TCs for Covid-19 management. SARS-CoV-2 and other coronaviruses depend mainly on the matrix metalloproteinases (MMPs) for their proliferation, cell adhesion and infiltration. The anti-inflammatory mechanisms of TCs are linked to different pathways. Briefly, TCs inhibit mitochondrial cytochrome c and caspase pathway with improvement of lymphopenia in early Covid-19. Specifically, minocycline is effective in reducing Covid-19 -related complications, through attenuation of cytokine storm as apparent by reduction of interleukin (IL)-6, IL-1, and tumor necrosis factor (TNF-α). Different clinical trials recommend the replacement of azithromycin by minocycline in the management of Covid-19 patients at high risk due to two main reasons: 1) minocycline does not prolong the QT interval and even inhibits ischemia induced-arrhythmia; 2) minocycline displays synergistic effect with chloroquine against SARS-CoV-2. Taken together, data presented here show that TCs, mainly doxycycline or minocycline, may be potential partners in Covid-19 management, derived pneumonia and related complications, like acute lung injury (ALI) and ARDS.